Gut Microbiota and Acute Central Nervous System Injury: A New Target for Therapeutic Intervention - Yuan, Bin; Lu, Xiao-jie; Wu, Qi (Frontiers in Immunology, 2021)
Acute central nervous system (CNS) injuries, including stroke, traumatic brain injury (TBI), and spinal cord injury (SCI), are the common causes of death or lifelong disabilities. Research into the role of the gut microbiota in modulating CNS function has been rapidly increasing in the past few decades, particularly in animal models. Growing preclinical and clinical evidence suggests that gut microbiota is involved in the modulation of multiple cellular and molecular mechanisms fundamental to the progression of acute CNS injury-induced pathophysiological processes. The altered composition of gut microbiota after acute CNS injury damages the equilibrium of the bidirectional gut-brain axis, aggravating secondary brain injury, cognitive impairments, and motor dysfunctions, which leads to poor prognosis by triggering pro-inflammatory responses in both peripheral circulation and CNS. This review summarizes the studies concerning gut microbiota and acute CNS injuries. Experimental models identify a bidirectional communication between the gut and CNS in post-injury gut dysbiosis, intestinal lymphatic tissue-mediated neuroinflammation, and bacterial-metabolite-associated neurotransmission. Additionally, fecal microbiota transplantation, probiotics, and prebiotics manipulating the gut microbiota can be used as effective therapeutic agents to alleviate secondary brain injury and facilitate functional outcomes. The role of gut microbiota in acute CNS injury would be an exciting frontier in clinical and experimental medicine.